Epistemic thinking in action : Evaluating and integrating online sources. - Sarit Barzilai; Anat Zohar (Cognition and Instruction, 2012)
This study examines epistemic thinking in action in order to shed light on the relation between students' personal epistemologies and their online learning practices. The study is based on observations of the learning behaviors of 6th-grade students (n = 38) during two online inquiry tasks. Data were collected through think-aloud protocols and retrospective epistemic interviews. The study examines how absolutist and evaluativist epistemic perspectives come into play in two key online inquiry strategies--evaluation of website trustworthiness and critical integration of multiple online sources. The study explores students' epistemic thinking on the cognitive and metacognitive levels and examines epistemic metacognitive knowledge about both persons and strategies. The findings demonstrate that epistemic thinking plays an important role in online inquiry learning. Participants' epistemic metacognitive knowledge regarding online learning strategies correlated with their epistemic cognition. Evaluativists significantly outperformed absolutists in the integration strategy but no significant differences were found in the evaluation strategy. Furthermore, there was evidence for considerable variability in students' epistemic thinking. The complex role of students' epistemic thinking in online learning is analyzed and discussed. (Contains 6 figures, 1 footnote and 8 tables.) Descriptors: Electronic Learning, Protocol Analysis, Online Courses, Learning Strategies, Metacognition, Epistemology, Grade 6, Inquiry, Task Analysis, Thinking Skills, Foreign Countries, Observation
Keywords: cognition; écriture et lecture numériques; évaluation; grade 6; stratégies d'apprentissage